Proceedings of the First Workshop on Computational Models Of Reference, Anaphora and Coreference 2018
DOI: 10.18653/v1/w18-0711
|View full text |Cite
|
Sign up to set email alerts
|

Event versus entity co-reference: Effects of context and form of referring expression

Abstract: Anaphora resolution systems require both an enumeration of possible candidate antecedents and an identification process of the antecedent. This paper focuses on (i) the impact of the form of referring expression on entity-vsevent preferences and (ii) how properties of the passage interact with referential form. Two crowd-sourced story-continuation experiments were conducted, using constructed and naturally-occurring passages, to see how participants interpret It and This pronouns following a context sentence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…This is confirmed in the study by Çokal et al (2018), where it was found to corefer to concrete entities both in production and interpretation, while this was biased towards non-NP, less salient antecedents. Likewise, in our previous study (Loáiciga et al, 2018) we find a preference for it to refer to entities and of this to refer to events. Similar results were also found by Wittenberg et al (2021) looking at it versus that, with the demonstrative being preferred for event coreference: this is interpreted as a "conceptual bundling" action of that, which would make event antecedents accessible by wrapping their complex structure in a simpler referring expression.…”
Section: Linguistic Descriptionssupporting
confidence: 65%
See 4 more Smart Citations
“…This is confirmed in the study by Çokal et al (2018), where it was found to corefer to concrete entities both in production and interpretation, while this was biased towards non-NP, less salient antecedents. Likewise, in our previous study (Loáiciga et al, 2018) we find a preference for it to refer to entities and of this to refer to events. Similar results were also found by Wittenberg et al (2021) looking at it versus that, with the demonstrative being preferred for event coreference: this is interpreted as a "conceptual bundling" action of that, which would make event antecedents accessible by wrapping their complex structure in a simpler referring expression.…”
Section: Linguistic Descriptionssupporting
confidence: 65%
“…The analysis for English should replicate the results of Loáiciga et al (2018), wherein we found a bias for It to corefer with entities and This with events, along with an effect of verb type, with verbs permitting alternation yielding more event coreference. The current analysis adds verbal aspect as a further predictor.…”
Section: Englishsupporting
confidence: 54%
See 3 more Smart Citations